Peran Pendidikan Progresivisme dalam Revolusi Industri 4.0 - Mu’minatus Fitriati Firdaus (LPPM IAIN Sorong, 2019)
Industrial revolution 4.0 comes out as shown in the digitalization of the industrial, economic, social and educational sectors. This reality shifts the dynamics of human life from humans as the center of life due to some functions are replaced by mechanical automation and technology digitalization. The main solution to compensate for these changes is by compiling students who are competent in their fields and able to solve life's challenges through education. Indonesian public awareness of the urgency of education has increased in recent years because they believe that education is a bridge for students who are ready to face life change. Progressive education encourages the formation of education that focuses on participants and focuses on students by providing the skills and knowledge needed. Thus, the purpose in progressive education must pay attention to students, educational goals, views on the meaning of learning, a student-based curriculum that is based upon both curriculum and the teacher's role for students.